2015
DOI: 10.1371/journal.pone.0123824
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Persistence with Injectable Therapy in Relapsing-Remitting Multiple Sclerosis: An 18-Year Observational Cohort Study

Abstract: Disease modifying therapies (DMTs) reduce the frequency of relapses and accumulation of disability in multiple sclerosis (MS). Long-term persistence with treatment is important to optimize treatment benefit. This long-term, cohort study was conducted at the Calgary MS Clinic. All consenting adults with relapsing-remitting MS who started either glatiramer acetate (GA) or interferon-β 1a/1b (IFN-β) between January 1st, 1996 and July 1st, 2011 were included. Follow-up continued to February 1st, 2014. Time-to-disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 36 publications
7
23
1
Order By: Relevance
“…This is consistent with previous Canadian studies 14,25,29. We suggest that this may be due to the availability of DMTs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous Canadian studies 14,25,29. We suggest that this may be due to the availability of DMTs.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is important to note that 57% of these individuals eventually resumed their initial DMT or started a different DMT, with the majority occurring within 1 year of discontinuation. Our findings are similar to results from a recent study at the Calgary MS Clinic which reported 54% of individuals restarted a DMT after an initial discontinuation 29. These temporary disruptions in therapy may have been due to monitoring recommendations for withholding doses for typically transient issues like liver enzymes or hematologic abnormalities.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, the age at diagnosis and gender ratio are similar to those reported in recent epidemiological surveys of MS in France [16, 17]. Moreover, age and disease duration at start of treatment, gender ratio, EDSS score and pre-treatment exacerbation rates were generally similar to those reported in other cohorts of patients starting GA or interferon-β in Spain [6], Britain [18] and Canada [4]. The rather long disease duration when GA was initiated (8 years) may reflect the fact that the study was initiated shortly after GA was first made available in France, and there was a reservoir of patients who could not be treated by interferon-β awaiting a new treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Nonetheless, between 2010 and 2014, after the introduction of oral DMTs, around one-third of patients in the national OFSEP patient registry for MS were not prescribed any DMT [15]. A high proportion of untreated patients who discontinue GA or interferon-β without another DMT being introduced has also been reported in a large Canadian cohort [4]. In general, clinical outcomes were worse in patients who discontinued GA than in those taking GA continuously, although it is not possible to determine the direction of any causality.…”
Section: Discussionmentioning
confidence: 99%
“…Continued treatment with IFN-β therapy is important to achieve maximum treatment efficacy, [8] but data from clinical trials and registries show that IFN-β therapies have a treatment discontinuation rate of between 14 and 44%, which may lead to disease reactivation [9]. The causes of IFN-β discontinuation may also change as a function of time.…”
Section: Introductionmentioning
confidence: 99%